The molecular mechanisms of curcumin's inhibitory effects on cancer stem cells. Issue 4 (30th September 2018) - Zendehdel, Elham; Abdollahi, Elham; Momtazi‐Borojeni, Amir Abbas; Korani, Mitra; Alavizadeh, Seyedeh Hoda; Sahebkar, Amirhossein
Abstract: Curcumin is a dietary polyphenol and a bioactive phytochemical that possesses anti‐inflammatory, antioxidant, anticancer, and chemopreventive properties, which make it capable of affecting multiple sites along the stem cell pathways to induce apoptosis in these cells. Curcumin's function is through suppression of cytokine release, especially the secretion of interleukins. Some of the predominant activities of stem cells include regeneration of identical cells and the ability to maintain the proliferation and multipotentiality. However, these cells could be stimulated to differentiate into specific cell types, leading to the development of tumors. Cancer stem cells (CSC) are capable of sustaining tumor formation and differentiation, and are normally characterized by self‐renewal mechanisms. Furthermore, these cells might be responsible for tumor relapse and resistance to therapy. Several studies have focused on the mechanisms of curcumin action in manipulating transcription factors, signaling pathways, CSC markers, microRNAs related to CSCs functions and apoptosis induction in various human cancer cells. In the present review, we aimed to summarize the reported molecular mechanisms of curcumin's effects on CSCs.